Metode Pembelajaran Tahfidz Al-Qur’an Bagi Anak Usia Dini Di Yayasan Darul Furqon Santok Kota Pariaman - Jivi, Rizka Amadea; Syamsurizal; Saputra, Edriagus; Delvia, Melda; Movitaria, Mega Adyna (Jurnal Pendidikan Islam, 2022)
This study aims to determine and analyze the use of the Al-Qur'an Learning Method at the Darul Furqon Pariaman Islamic Boarding School in improving student learning in schools in improving the learning process by tahfiz teachers. The method used in this research is descriptive qualitative analysis approach in collecting data, pictures and interviews. The method used by Tahfizh Toddler Darul Furqon Santok Kota Pariaman asatidzah uses the Pakistani method including the talaqqi method, the Sabaq method, the sabki method, and the manzil method. The method used is very effective and fast for early childhood children in memorizing verses of the Qur'an. It is evident from parents who are very enthusiastic in supervising and supporting their children to enter this Tahfizh Al-Qur'an Educational Institute.